2017
DOI: 10.1007/s40675-017-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work: Disrupted Circadian Rhythms and Sleep—Implications for Health and Well-being

Abstract: Purpose of review Our 24/7 society is dependent on shift work, despite mounting evidence for negative health outcomes from sleep displacement due to shift work. This paper reviews short- and long-term health consequences of sleep displacement and circadian misalignment due to shift work. Recent findings We focus on four broad health domains: metabolic health; risk of cancer; cardiovascular health; and mental health. Circadian misalignment affects these domains by inducing sleep deficiency, sympathovagal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
232
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(263 citation statements)
references
References 111 publications
4
232
1
7
Order By: Relevance
“…42,43 For instance, if interested in the pathway A→B→C, the mediation proportion using Equations (2) and (3) is MP = Indirect*100/Total = ( 12 × 23 )*100/( 12 × 23 + 13 ). In this example, the direct effect 13 should be in the same direction as the indirect effect to obtain a meaningful positive MP. 44 = ∑ (1)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 For instance, if interested in the pathway A→B→C, the mediation proportion using Equations (2) and (3) is MP = Indirect*100/Total = ( 12 × 23 )*100/( 12 × 23 + 13 ). In this example, the direct effect 13 should be in the same direction as the indirect effect to obtain a meaningful positive MP. 44 = ∑ (1)…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of inflammatory biomarkers (e.g., C-reactive protein [CRP], interleukin-6 [IL-6], interleukin-8 , interleukin-10 [IL-10], tumor necrosis factor-alpha [TNF-], and white blood cells [WBCs]) are associated with risk and prognosis of chronic conditions, including cardiovascular disease [1][2][3] and cancer. [4][5][6][7][8][9] Recent studies have also suggested that periodontal disease [10][11][12] and sleep behavior 13,14 may increase the risk of chronic disease onset and progression through inflammatory mechanisms, and may be linked to each other. [15][16][17] Current evidence linking periodontal disease 18,19 and sleep behavior [20][21][22] to systemic inflammation focused primarily on CRP with limited evidence for WBCs or their products as inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the reported higher TSH in the night shift workers is attributed to disruption of the circadian rhythm (James et al 2017). Under physiological conditions, TSH shows circadian rhythmicity, with its peak at mid-night (2:00-4:00 a.m.) and trough at (4:00-8:00 p.m.) (Weibel et al 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Shift work is related to disturbances in the circadian rhythm and sleep disturbances, which are suspected to contribute to mental health problems (1)(2)(3)(4). A metaanalysis of 11 primary studies concluded that night shift work was significantly associated with an increased risk of depression (5), and a prospective study found a 'flexible/non-regulated' schedule prospectively associated with antidepressant prescription among females (6).…”
mentioning
confidence: 99%